2013
DOI: 10.1097/pcc.0b013e31828a7113
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Modified Ultrafiltration Hemodynamic Impact by Pressure Recording Analytical Method During Pediatric Cardiac Surgery

Abstract: According to Pressure Recording Analytical Method assessment, modified ultrafiltration acutely improves myocardial function, as shown by a 10% increase of systemic arterial pressure, stroke volume index, and cardiac index. This effect is more pronounced in smaller sized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Data were collected after anesthesia induction, at the end of CPB, before fluid administration and after fluid administration. Overall, median-IQR PRAM SVI values (23 mlÁm À2 , [19][20][21][22][23][24][25][26][27] were significantly higher than bioreactance SVI (15 mlÁm À2 , 12-25, P = 0.0001). Correlation (r 2 ) between the two methods was 0.15 (P = 0.0003).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Data were collected after anesthesia induction, at the end of CPB, before fluid administration and after fluid administration. Overall, median-IQR PRAM SVI values (23 mlÁm À2 , [19][20][21][22][23][24][25][26][27] were significantly higher than bioreactance SVI (15 mlÁm À2 , 12-25, P = 0.0001). Correlation (r 2 ) between the two methods was 0.15 (P = 0.0003).…”
Section: Discussionmentioning
confidence: 83%
“…Percentage error was 91.7%. Baseline SVI appeared to be similar, but PRAM SVI was systematically greater than bioreactance thereafter, with the highest gap after the fluid loading phase: 13 (12)(13)(14)(15)(16)(17)(18) mlÁm À2 vs. 23 (19)(20)(21)(22)(23)(24)(25) mlÁm À2 , respectively, P = 0.0013. A multivariable regression model showed that a significant independent inverse correlation with patients' body weight predicted the CI difference between the two methods after fluid challenge (b coefficient À0.12, P = 0.013).…”
Section: Discussionmentioning
confidence: 92%
“…Clinical investigations of the use of MUF in children undergoing cardiac surgery have shown many benefits including reduction of fluid overload, reduced inflammatory mediators and complement activation, improved recovery of cardiac, pulmonary, and cerebral function, and reduced postoperative duration of mechanical ventilation and hospitalization (2)(3)(4)(5)(6)(7)(8)(9). In addition, higher hematocrit and improved coagulation in patients receiving MUF reduce the need for postoperative transfusion and bleeding complications (10).…”
Section: Referencesmentioning
confidence: 99%
“…Pressure recording analytical method (PRAM, Vygon, Vytech, Padova, Italy) is a direct systemic hemodynamic monitoring technique based on mathematical analysis of the arterial waveform to derive PPV and other hemodynamic parameters such as stroke volume and cardiac output . It provides plausible value in measuring cardiac output and tracking its changes after fluid infusion in congenital heart disease children …”
Section: Introductionmentioning
confidence: 99%